Mother’s Knowledge Level, Eating Habits and Nutritional Status of Children (3-5 years) (INCH : Journal of Infant and Child Healthcare, 2022)
Nutritional status is a measure of a person’s body condition that seen from the food consumed and the use of nutrients in the body. One of assessing the nutritional status of under five years old children is by measuring the weight index according to age (W/U) with the result categories of over nutrition, good nutrition, under nutrition and poor nutrition. The purpose of this study was to determine the level of mother’s knowledge, eating habits and nutritional status of children (3-5 years) in Pinang Sebatang Timur Village, Siak Regency. The study design was a cross sectional design which involved 45 children in January 2019. This study employed a mother’s knowledge level and eating habits questionare. the result showed a mother’s knowledge level was sufficient category (73,9%), eating habits were complete (3 times a day) (80,4%) and nutritional status was in good category (50,9%). Suggestions for further research are expected that researchers can explore eating habits to obtain a broader picture and results.